Mit hemmelige liv - En victoriansk sexodyssé - Søndergaard, Nina (Slagmark - Tidsskrift for idéhistorie, 2018)
The bulky and anonymous sexual autobiography My Secret Life from Victorian England is here read very closely in order to shed new light on Victorian sexual practices and views on sexuality. Some of the examples dealt with are nudity during intercourse, female orgasm and fulfilment through intercourse as preferable over masturbation – all examples of practices which force us to question the traditional views on Victorian sexual life. This reassessment of sexuality in Victorian times is not widely shared. Scholars have dealt with the work as pornography (Gubar), pure fiction (Gibson) or a credible depiction of contemporary daily life containing pornographic elements, namely the descriptions of the women’s pleasure (Marcus). In the article it is argued that the author’s intention was to give female sexuality a voice.